Estimating the Value of Water-Use Efficiency in the Intermountain West - Groves, David G. (RAND Corporation, 2008)
This report presents an economic framework for estimating a water agency's avoided costs and environmental benefits of increasing water-use efficiency. The report demonstrates this framework by evaluating the benefits of Denver Water's efficiency programs and utilizes an exploratory modeling approach to accommodate significant uncertainty. The analysis highlights the importance of considering both long- and short-run costs and benefits.